2020
DOI: 10.5194/esurf-8-637-2020
|View full text |Cite
|
Sign up to set email alerts
|

The role of frost cracking in local denudation of steep Alpine rockwalls over millennia (Eiger, Switzerland)

Abstract: Abstract. Denudation of steep rockwalls is driven by rock fall processes of various sizes and magnitudes. Rockwalls are sensitive to temperature changes mainly because thermo-cryogenic processes weaken bedrock through fracturing, which can precondition the occurrence of rock fall. However, it is still unclear how the fracturing of rock together with cryogenic processes impacts the denudation processes operating on steep rockwalls. In this study, we link data on long-term rockwall denudation rates at the Eiger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…This was predicted by numerical modelling (e.g. Anderson et al, 2013;Egholm et al, 2015;Hales & Roering, 2007), and shown by cosmogenic nuclide (Mair et al, 2020) and monitoring studies (Hartmeyer et al, 2020). Thus, the few metres of periglacial erosion predicted in our experiments might strongly underestimate real-world headwall retreat, at least in temperate mountain ranges.…”
Section: Temporal Variations In Erosion Ratesupporting
confidence: 67%
“…This was predicted by numerical modelling (e.g. Anderson et al, 2013;Egholm et al, 2015;Hales & Roering, 2007), and shown by cosmogenic nuclide (Mair et al, 2020) and monitoring studies (Hartmeyer et al, 2020). Thus, the few metres of periglacial erosion predicted in our experiments might strongly underestimate real-world headwall retreat, at least in temperate mountain ranges.…”
Section: Temporal Variations In Erosion Ratesupporting
confidence: 67%
“…As a point of reference, Benjamin et al (2020) provide an assessment of efforts to observe and measure rockfall events contributing to cliff erosion and thus to downslope delivery of particles. The frequency and magnitude of these events may vary widely, from the chronic activity of small rockfall events to large infrequent events, depending on the geological and environmental factors that influence the mechanisms of weathering and failure (Luckman, 2013;Strunden et al, 2015;Mair et al, 2020). The frequency of occurrence of rockfall volume typically varies as an approximate inverse power function of volume, where the specific relation depends on the spatial coverage and temporal duration of the data set (Benjamin et al, 2020).…”
Section: Line Sourcementioning
confidence: 99%
“…As a point of reference, Benjamin et al (2020) provide an assessment of efforts to observe and measure rockfall events contributing to cliff erosion and thus to downslope delivery of particles. The frequency and magnitude of these events may vary widely, from the chronic activity of small rockfall events to large infrequent events, depending on the geological and environmental factors that influence the mechanisms of weathering and failure (Luckman, 2013;Strunden et al, 2015;Mair et al, 2020). The frequency of occurrence of rockfall volume typically varies as an approximate inverse power function of volume, where the specific relation depends on the spatial coverage and temporal duration of the data set (Benjamin et al, 2020).…”
Section: Line Sourcementioning
confidence: 99%